Effects of Spiruline (Spirulina platensis) Supplementation on Oxidative Stress Markers, Biochemical Characteristics, and Hematological Parameters in Rabbit (Oryctolagus cuniculus) Does - Momo, Chongsi Margaret Mary; Adam, Mahamat Tahir Markhous; Herve, Tchoffo; Narcisse, Vemo Bertin; Ferdinand, Ngoula; Joseph, Tchoumboue (Asian Journal of Agriculture and Rural Development, 2021)
The present study was carried out in order to evaluate the effects of feed supplementation with spiruline powder on the oxidative stress markers, biochemical characteristics, and hematological parameters in rabbit doe. Twenty-one nulliparous and sexually mature does (7–8 months old) were distributed into three groups of seven does each, comparable in terms of body weight. After a week of feeding with experimental feed, does of each group were mated. During the trial, does of group 1 (control group) were fed ad libitum with a feed free from spiruline (control feed), while those of groups 2 and 3 received the control feed supplemented with spiruline powder at 0.6 and 1.2%, respectively. Immediately after parturition, blood was collected for analyses of hematological, biochemical, and oxidative stress parameters. Studied parameters included serum concentrations of total proteins, cholesterol, aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT), creatinine, and urea; malondialdehyde, reduced glutathione, catalase, and superoxide dismutase; and hematological parameters. The total protein concentration, number of white and red blood cells, platelets, hemoglobin, hematocrit, and mean corpuscular volume were significantly (P<0.05) higher in does treated compared to control. Oxidative stress parameters were comparable (P>0.05) among treatments. Hence, these results show that feed supplementation with spirulina powder can improve rabbit doe health, notably at 1.2%, since optimal results were obtained at this percentage.